2016
DOI: 10.1016/j.maturitas.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The oldest carers: A narrative review and synthesis of the experiences of carers aged over 75 years

Abstract: As populations age, numbers of older carers are increasing. These carers play a vital role in supporting others, often partners or spouses with dementia. This narrative review synthesised peer-reviewed evidence published over the last two decades concerning the experiences of carers aged over 75 years, specifically exploring whether their experiences differ from those of younger carers. Four electronic databases were searched and 4102 publications were identified. Eighteen studies involving over one thousand c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 37 publications
(109 reference statements)
6
45
1
4
Order By: Relevance
“…Regarding interventions to support informal caregivers, other systematic reviews mainly report that these should be approachable and adjusted to the needs of caregivers, to prevent the most vulnerable caregivers from being excluded (Applebaum & Breitbart, ; Bunn et al., ; Dias et al., ; Greenwood & Smith, ; Jones, Edwards, & Hounsome, ; Sansoni et al., ; Schoenmakers et al., ; Seal et al., ; Wheelwright, Darlington, Hopkinson, Fitzsimmons, & Johnson, ). To adjust interventions to the caregivers’ needs, further research is needed to compare caregivers of different gender and demographic backgrounds (Greenwood & Smith, , ; Sansoni et al., ; Schoenmakers et al., ). Also, they suggest more longitudinal research focusing on caring dyads and caregiving networks (Applebaum & Breitbart, ; Greenwood & Smith, ), because of their important influence on caregiver's psychosocial problems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding interventions to support informal caregivers, other systematic reviews mainly report that these should be approachable and adjusted to the needs of caregivers, to prevent the most vulnerable caregivers from being excluded (Applebaum & Breitbart, ; Bunn et al., ; Dias et al., ; Greenwood & Smith, ; Jones, Edwards, & Hounsome, ; Sansoni et al., ; Schoenmakers et al., ; Seal et al., ; Wheelwright, Darlington, Hopkinson, Fitzsimmons, & Johnson, ). To adjust interventions to the caregivers’ needs, further research is needed to compare caregivers of different gender and demographic backgrounds (Greenwood & Smith, , ; Sansoni et al., ; Schoenmakers et al., ). Also, they suggest more longitudinal research focusing on caring dyads and caregiving networks (Applebaum & Breitbart, ; Greenwood & Smith, ), because of their important influence on caregiver's psychosocial problems.…”
Section: Discussionmentioning
confidence: 99%
“…To adjust interventions to the caregivers’ needs, further research is needed to compare caregivers of different gender and demographic backgrounds (Greenwood & Smith, , ; Sansoni et al., ; Schoenmakers et al., ). Also, they suggest more longitudinal research focusing on caring dyads and caregiving networks (Applebaum & Breitbart, ; Greenwood & Smith, ), because of their important influence on caregiver's psychosocial problems. The results of other systematic reviews support our findings that all except two studies showed a tendency towards a higher prevalence of caregiver psychosocial problems, such as depression, compared to the general population (Bachner et al., ; Goldzweig et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second stage involved hand searching these items for those that focused on older former carers. While the initial intention was to base the definition of 'old' on the criteria used to define older carers, these were discarded in the light of the evidence that there is no set definition of an older carerdefinitions vary from 50+ to 80+ (Milne & Hatzidimitriadou, 2002, Carers Trust, 2015, Manthorpe et al 2015, Greenwood & Smith 2016. As 60+ is routinely used in data collection (United Nations Department of Economic and Social Affairs, 2013), this was used to select items about 'older former carers'.…”
Section: Review Methodsmentioning
confidence: 99%